Antidiarrhoeal Activity of the Alcoholic Extract of the Leaves of Butea frondosa Koen. Ex Roxb - Banji, D. (Medknow Publications, 2010)
The study evaluated the antidiarrhoeal property of the alcohol extract of Butea frondosa leaf on mice and rats. Studies revealed that at a dose of 25 and 75 mg/kg a considerable reduction in the extent of diarrhoea was observed but at a dose of 100 mg/kg the animals appeared completely constipated when subjected to castor oil induced diarrhoea and intestinal motility model. Therefore, Butea frondosa can be regarded as an effective antidiarrhoeal.